2015
DOI: 10.1016/j.ttbdis.2015.03.017
|View full text |Cite
|
Sign up to set email alerts
|

U.S. public's experience with ticks and tick-borne diseases: Results from national HealthStyles surveys

Abstract: Surveillance data indicate that tick-borne diseases (TBDs) are a substantial public health problem in the United States, yet information on the frequency of tick exposure and TBD awareness and prevention practices among the general population is limited. The objective of this study was to gain a more complete understanding of the U.S. public's experience with TBDs using data from annual, nationally representative HealthStyles surveys. There were 4728 respondents in 2009, 4050 in 2011, and 3503 in 2012. Twenty-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
53
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(57 citation statements)
references
References 30 publications
3
53
1
Order By: Relevance
“…60 There are a myriad of explanations for poor adherence, ranging from inconvenience, to concern about product safety, to perceptions and beliefs about the threat of Lyme disease. Unfortunately, there are no clear solutions to this problem.…”
Section: Side View Front Viewmentioning
confidence: 99%
“…60 There are a myriad of explanations for poor adherence, ranging from inconvenience, to concern about product safety, to perceptions and beliefs about the threat of Lyme disease. Unfortunately, there are no clear solutions to this problem.…”
Section: Side View Front Viewmentioning
confidence: 99%
“…The infection tends to manifest as a general influenza-like illness, and onset of a rash is rare (12), so persons may be less likely to visit a doctor unless more severe symptoms emerge or they are aware of a recent tick bite and the presence of tickborne diseases in the area. Awareness of nonLyme disease tickborne illnesses is startlingly low, even in parts of the country where ehrlichiosis cases outnumber Lyme disease cases (33)(34)(35). One study found that >50% of respondents in the United States had heard of Lyme disease, whereas only 1.4% had heard of ehrlichiosis (35).…”
Section: Discussionmentioning
confidence: 99%
“…Awareness of nonLyme disease tickborne illnesses is startlingly low, even in parts of the country where ehrlichiosis cases outnumber Lyme disease cases (33)(34)(35). One study found that >50% of respondents in the United States had heard of Lyme disease, whereas only 1.4% had heard of ehrlichiosis (35). As a consequence of these factors, when active screening for ehrlichial infections is performed, the resulting case rates are often much higher than those reported to governmental agencies (3,36,37).…”
Section: Discussionmentioning
confidence: 99%
“…Consequent upon this variation in the global distribution, availability and density in population of the tick vectors and reservoir hosts, the prevalence of tick-borne rickettsial pathogens varies from one ecological site to the other [8][9][10][11]. Across the globe, there are many studies that are currently being carried out with the sole aim of determining the significance for human health of tickborne diseases.…”
Section: Introductionmentioning
confidence: 99%